2021
DOI: 10.1111/1471-0528.16781
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery embolisation or myomectomy for women with uterine fibroids wishing to avoid hysterectomy: a cost–utility analysis of the FEMME trial

Abstract: To assess the cost-effectiveness of uterine artery embolization (UAE) and myomectomy for women with symptomatic uterine fibroids wishing to avoid hysterectomy. DesignEconomic evaluation alongside the FEMME randomised controlled trial. Setting UK hospitals. PopulationPremenopausal women who had symptomatic uterine fibroids amenable to UAE or myomectomy wishing to avoid hysterectomy. 254 women were randomised to UAE (127) and myomectomy (127). MethodsA within trial cost-utility analysis was conducted from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
(90 reference statements)
0
10
1
Order By: Relevance
“…The data from the present study showed that myomectomy was cost‐effective in the UK healthcare setting 24 ; however, this does not take into account that UAE is less invasive. Given that both procedures are clinically effective, UAE may be more attractive in low‐resource settings as it requires a shorter hospital stay (median 4 days compared with 2 days) and has the potential to be completed as an outpatient procedure.…”
Section: Discussioncontrasting
confidence: 58%
“…The data from the present study showed that myomectomy was cost‐effective in the UK healthcare setting 24 ; however, this does not take into account that UAE is less invasive. Given that both procedures are clinically effective, UAE may be more attractive in low‐resource settings as it requires a shorter hospital stay (median 4 days compared with 2 days) and has the potential to be completed as an outpatient procedure.…”
Section: Discussioncontrasting
confidence: 58%
“…A cost-utility assessment of the two procedures based on the FEMME trial has been published elsewhere. [15] UAE is dominated by myomectomy and would not be considered a cost-effective alternative over myomectomy, but this does not take into account any potential preference for a less invasive procedure. There is such a small difference in costs between the two procedures, fully informed patient preference should be acknowledged, and women should have the option to choose between the two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…The recent FEMME trial that evaluated the cost utility of myomectomy versus UAE showed UAE to be associated with higher costs (difference of 645 pounds) in 4 year horizon 9 These results point out that the short-term results of UAE are good, while the long-term results of myomectomy are better, as UAE may require frequent reinterventions.…”
Section: Uae For Fibroidsmentioning
confidence: 96%